Attitudes and Actions Teacher Preparation Programs in ESL and IEPs - Perkins, Samuel S. ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
The role of participant attitudes in the effectiveness of two teacher education program types, English-as-a-Second-Language (ESL) and intensive English programs (IEPs), are discussed. Three factors are viewed as influencing participant attitudes: professional separation of ESL and IEP instruction as fields of study; physical separation of ESL and IEP programs and teacher trainees; and unrealistic expectations of ESL and IEP teachers. It is argued that IEPs are often afforded lesser status in higher education in general, with college students in IEPs often not earning academic credit and the faculty teaching in (IEPs) often not attaining full faculty status. In addition, ESL teachers are seen as unaware of/uninterested in their IEP counterparts' professional development activities or ideas about teaching. Physical separation of trainees in the two program types and lack of recent classroom experience on the part of ESL teacher educators tend to promote attitudinal separation. Limited length of ESL programs and IEPs and differential scheduling of the two programs within one institution are also seen as disadvantageous. Separation of teacher trainees into distinct programs is therefore found counterproductive. Suggestions for developing and maintaining constructive attitudes among teacher educators in both program types are offered. (Contains 7 references.) (MSE)
ERIC Note: Paper presented at the Annual Meeting of the Sunshine State Teachers of English to Speakers of Other Languages (22nd, Fort Lauderdale, FL, May 7-9, 1998).
Practitioners.
Teachers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Faculty; English (Second Language); Higher Education; Intensive Language Courses; Language Teachers; Program Effectiveness; Second Language Instruction; Student Attitudes; Teacher Attitudes; Teacher Education; Tenure; Reports, Descriptive; Speeches/Meeting Papers